Inhibition of Protein Glycation by Tiger Milk Mushroom [Lignosus rhinocerus (Cooke) Ryvarden] and Search for Potential Anti-diabetic Activity-Related Metabolic Pathways by Genomic and Transcriptomic Data Mining - Yap, Hui Yeng Yeannie; Tan, Nget Hong; Ng, Szu Ting; Tan, Chon Seng; Fung, Shin Yee (Frontiers Media, 2018)
Naturally occurring anti-glycation compounds have drawn much interest in recent years as they show potential in reducing or preventing the risk of chronic complications for diabetic patients. In this study, annotation of the genome-transcriptome data from tiger milk mushroom (Lignosus rhinocerus, syn. Lignosus rhinocerotis) to PlantCyc enzymes database identified transcripts that are related to anti-diabetic properties, and these include genes that are involved in carotenoid and abscisic acid biosynthesis as well as genes that code for glyoxalase I, catalase-peroxidases, and superoxide dismutases. The existence of these genes suggests that L. rhinocerus may contain bioactive compound(s) with anti-glycation properties that can be exploited for management of diabetic complications. A medium-molecular-weight (MMW) fraction which was obtained from a combination of cold water extraction and Sephadex® G-50 (fine) gel filtration chromatography of L. rhinocerus sclerotia powder was demonstrated to exhibit potent anti-glycation activity. The fraction specifically inhibited the formation of Nε-(carboxymethyl)lysine, pentosidine, and other advanced glycation end-product (AGE) structures in a human serum albumin-glucose system, with an IC50 value of 0.001 mg/ml, almost 520 times lower than that of the positive control, aminoguanidine hydrochloride (IC50 = 0.52 mg/ml). Its ability to suppress protein glycation may be partly associated with its strong superoxide anion radical scavenging activity (10.16 ± 0.12 mmol TE/g). Our results suggest that the MMW fraction of L. rhinocerus shows potential to be developed into a potent glycation inhibitor for preventing AGE-mediated diabetic complications.